The Windmill technique avoids manual removal of the retained placenta—A new solution for an old problem. (August 2017) - Hinkson, Larry; Suermann, Mia Amelie; Hinkson, Susan; Henrich, Wolfgang
Abstract: Objective: The primary objective is to assess the reduction in manual removal of placenta with the Windmill technique of placenta delivery in patients with retained placenta. Design: The Windmill technique involves the application of continuous 360° umbilical cord traction and rotation in such a manner as to be perpendicular to the direction of the birth canal at the level of the introitus. This rotation through 360 ° is repeated slowly with movement akin to the motion of the blades of a windmill. We performed a 3-year retrospective case-control study at the Charité University Hospital in Berlin. Patients with a retained placenta more than 30 min following failed traditional interventions were consented and offered the Windmill technique of placenta delivery. Study cases were compared to controls where an operative manual removal of placenta was performed. Patients with suspected placenta implantation problems, uterine atony, bleeding due to vaginal tract injury and coagulation disturbances were excluded. Results: Over the study period 14 patients were recruited to the study arm and 17 patients were in the control group. With the Windmill technique for retained placenta, 86% (12/14, p < 0.001) of patients avoided invasive operative manual removal of the placenta in theatre. There was a statistically significant reduction in mean blood loss (429 ml vs 724 ml, p = 0.001) and mean postoperative fall in hemoglobin values (1.3 g/dl vs 2.5 g/dl, p = 0.04). There was a reduction in the time to delivery of the placenta, antibiotic prophylaxis and use of general anesthesia. Conclusion: The Windmill technique for the delivery of the retained placenta is a simple, safe, effective and easy to teach technique that reduces invasive operative manual removal of the placenta, postpartum blood loss and delay in the placenta delivery. This innovative technique can also be a lifesaving intervention especially in areas with limited or no access to operative facilities.